2008
DOI: 10.2503/jjshs1.77.388
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar Differentiation Identified by SSR markers and the Application for Polyploid Loquat Plants

Abstract: Here we established a DNA marker-based method to identify cultivars of loquat (Eriobotrya japonica Lindl.) using simple sequence repeat (SSR) markers derived from pears and apples. A total of 24 loquat cultivars commercially grown in Japan were used for genetic identification, including 15 diploid-, 6 triploid-, and 3 tetraploid cultivars. Analysis using the 88 SSR markers derived from pears and apples, which belong to the same subfamily (family Rosaceae, subfamily Maloideae) as the loquat, indicated that 26 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
4
12
0
Order By: Relevance
“…In other fruit trees like loquat (Eriobotrya japonica Lindl.) triploidy of a few varieties has been also confirmed using 3-allele producing SSR primers (Watanabe et al 2008). Both SSR and ISSR markers found no differentiation between 'Eureka' and 'Lisbon' lemons, and between 'Frost Valencia' and 'Washington Navel' sweet oranges in agreement with results of previous studies on citrus cultivar identification (Ahmad et al 2003;Uzun et al 2009).…”
Section: Ssr Unique Allelessupporting
confidence: 86%
“…In other fruit trees like loquat (Eriobotrya japonica Lindl.) triploidy of a few varieties has been also confirmed using 3-allele producing SSR primers (Watanabe et al 2008). Both SSR and ISSR markers found no differentiation between 'Eureka' and 'Lisbon' lemons, and between 'Frost Valencia' and 'Washington Navel' sweet oranges in agreement with results of previous studies on citrus cultivar identification (Ahmad et al 2003;Uzun et al 2009).…”
Section: Ssr Unique Allelessupporting
confidence: 86%
“…And there's three alleles of 238 bp, 236 bp and 230 bp with primer Hi15h12 of A322 (Figure 3). Similar results were obtained by Watanabe et al (2008). New alleles emerged as compared diploid and each one of triploid individuals, indicating foreign genes maybe introgressed along with the formation progress of triploid individuals.…”
Section: Ssr (Simple Sequence Repeat) Analysis Of Natural Triploid Losupporting
confidence: 75%
“…2000; Cai 2000; Vilanova et al 2001;Soriano et al 2005;Dong 2008;Qiao 2008;Watanabe et al 2008;Yang 2009). These studies significantly enhanced our understanding about the distribution and structure of genetic diversity in loquat germplasm around the world.…”
mentioning
confidence: 99%
“…In our preliminary experiments, some SSR markers originating from apple and pear that have already been applied to loquat (He et al, 2011;Soriano et al, 2005;Watanabe et al, 2008) were evaluated for loquat materials, including indigenous accessions, in this study. It was found that these SSR markers sometimes had disadvantages, for example, unstable amplification, difficulty in scoring and a small number of SSR alleles, maybe due to different plant materials and analysis systems; therefore, we screened additional SSR markers suitable for this study.…”
Section: Ssr Analysismentioning
confidence: 99%
“…Recent reports indicated that SSR markers could be applicable across genera within the sub-family Spiraeoideae, tribe Pyreae, which includes apple, pear, loquat, and quince (Fukuda et al, 2007;Liebhard et al, 2002;Soriano et al, 2005;Yamamoto et al, 2001Yamamoto et al, , 2004. In loquat, SSR markers originating from apple have been used to analyze cultivars present in Europe (Soriano et al, 2005), cultivars present in China (He et al, 2011), and polyploid cultivars present in Japan (Watanabe et al, 2008); however, there have been few reports on the genetic diversity of East Asian loquats.…”
Section: Introductionmentioning
confidence: 99%